2019
DOI: 10.1039/c8cp06943c
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced microwave absorption properties of PMMA modified MnFe2O4–polyaniline nanocomposites

Abstract: Nanocomposites consisting of polymethyl methacrylate modified MnFe2O4 prepared by solution combustion synthesis and polyaniline exhibit enhanced electromagnetic interference (EMI) shielding property.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…In recent years, the low cost, environmentally friendly nature, chemical, and physical properties of spinel structured complex metal oxides containing two or more types of cations following controlled size and shape have been receiving considerable interest for multifaceted applications . It is reported that magnetic dipoles provided by ferrites having a high value of magnetic permeability and considerable magnetic loss to reduce unwanted EM radiation. , However, ferrite cannot effectively absorb electromagnetic wave due to weak magnetic loss in the high-frequency region due to the Snoek’s limit. Recently, cobalt based nonferritic spinel oxides, MCo 2 O 4 (MNi, Zn and Mn) have been receiving considerable amount of attention due to their several structure/composition-dependent advantages. MCo 2 O 4 can be prepared by variety of methods, such as hydrothermal, solvothermal, sol–gel, solid-state, thermal decomposition of organometallic compounds, spray pyrolysis, microwave plasma, etc. These nonferrites find application in a variety of fields, such as lithium-ion batteries, supercapacitors, fuel cell, sensors, electrocatalysts, and magnetic materials, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the low cost, environmentally friendly nature, chemical, and physical properties of spinel structured complex metal oxides containing two or more types of cations following controlled size and shape have been receiving considerable interest for multifaceted applications . It is reported that magnetic dipoles provided by ferrites having a high value of magnetic permeability and considerable magnetic loss to reduce unwanted EM radiation. , However, ferrite cannot effectively absorb electromagnetic wave due to weak magnetic loss in the high-frequency region due to the Snoek’s limit. Recently, cobalt based nonferritic spinel oxides, MCo 2 O 4 (MNi, Zn and Mn) have been receiving considerable amount of attention due to their several structure/composition-dependent advantages. MCo 2 O 4 can be prepared by variety of methods, such as hydrothermal, solvothermal, sol–gel, solid-state, thermal decomposition of organometallic compounds, spray pyrolysis, microwave plasma, etc. These nonferrites find application in a variety of fields, such as lithium-ion batteries, supercapacitors, fuel cell, sensors, electrocatalysts, and magnetic materials, etc.…”
Section: Introductionmentioning
confidence: 99%
“…7 It is reported that magnetic dipoles provided by ferrites having a high value of magnetic permeability and considerable magnetic loss to reduce unwanted EM radiation. 8,9 However, ferrite cannot effectively absorb electromagnetic wave due to weak magnetic loss in the high-frequency region due to the Snoek's limit. 10−13 Recently, cobalt based nonferritic spinel oxides, MCo 2 O 4 (MNi, Zn and Mn) have been receiving considerable amount of attention due to their several structure/ composition-dependent advantages.…”
Section: ■ Introductionmentioning
confidence: 99%
“…4a) is associated with the (021) lattice plane of JCPDS card no. 53-1891, both are associated with the orthorhombic crystal structure [47][48][49][50][51][52].This small degree of crystallinity is ascribed to the periodicity of benzenoid and quinoid rings present in the PANI structure [53,54]. Furthermore, P-3 was subjected to the FT-IR analysis as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that this dielectric loss peak shifts to a lower frequency of 1.22GHz with the addition of MWCNTs to enhance ε ′′ in a low frequency domain. Moreover, the magnetic loss tangent of (ZCFO/MNFO)@C-MWCNTs in Figure 8b indicates a strong magnetic loss absorption of microwave, particularly in the low frequency domain; this is mainly due to the increased μ ′′ of the quaternary hybrid for the reason mentioned above [49].…”
Section: Resultsmentioning
confidence: 99%